Asymptotic expansion of the inverted matrix variate Dirichlet distribution (2004)
ABSTRACT: In this paper, the inverted matrix variate Dirichlet distribution for both the real and the complex cases are defined and some of their properties are studied. Also, the asymptotic expansions of the probability density functions of the inverted matrix variate Dirichlet distributions, for real and complex cases, are derived.